2017
DOI: 10.7249/rr1819
|View full text |Cite
|
Sign up to set email alerts
|

Technical Quality and Clinical Acceptability of a Utilization Review Guideline for Occupational Conditions: ODG® Treatment Guidelines by the Work Loss Data Institute

Abstract: Limited Print and Electronic Distribution RightsThis document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…However, participants reported that the CPGs omitted common clinical situations and contained recommendations of uncertain clinical validity. Similar results have been found with disability-related CPGs …”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, participants reported that the CPGs omitted common clinical situations and contained recommendations of uncertain clinical validity. Similar results have been found with disability-related CPGs …”
Section: Introductionsupporting
confidence: 89%
“…Since the release of AGREE II, studies have reported that high AGREE II scores do not guarantee that the resulting CPG recommendations are optimal. [23][24][25][26][27] For example, Nuckols et al 24 evaluated the technical quality and acceptability of 5 musculoskeletal CPGs. Use of the AGREE II tool resulted in high quality scores (eg, rigor domain scores >80%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores on the domain of Editorial independence show an ‘all or nothing’ pattern across CPGs. Other studies 5,6,8,9,35 similarly show relatively lower scores on this domain. 0% scores on this domain do not necessarily indicate a lack of editorial independence.…”
Section: Resultsmentioning
confidence: 69%
“…8 For instance, AGREE II was used to appraise official disability guidelines, and achieved a high score (eg, the clarity of the presentation domain score was 75%; scale: 0-100%). 19 However, expert clinicians reported that the recommendations have less utility in the non-guideline development setting. In addition, for several themes, the content was of doubtful https://doi.org/10.2147/RMHP.S378684…”
Section: Introductionmentioning
confidence: 99%